2020
DOI: 10.1111/jcmm.15916
|View full text |Cite
|
Sign up to set email alerts
|

CSF‐1R inhibition disrupts the dialog between leukaemia cells and macrophages and delays leukaemia progression

Abstract: Research in the last few years has revealed that leukaemic cells can remodel the bone marrow niche into a permissive environment favouring leukaemic stem cell expansion. Tumour‐associated macrophages (TAMs) are prominent components of the tumour microenvironment and play an important role in the onset and progression of solid tumours. However, little is known about their role in the development of acute lymphoblastic leukaemia (ALL). Using a unique mouse model of T‐ALL induced by injection of EL4 T‐cell lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…The use of CSF-1R inhibitors in AML patients can inhibit the secretion of multiple cytokines in support cells and block their protective effects on AML cells. Similarly, our research also shows that targeting macrophages can delay the progression of ALL in mice [42]. Therefore, targeting CSF-1R combined with chemotherapeutic drugs can simultaneously kill leukemia cells, destroy the bone marrow microenvironment that they depend on for survival and enhance the antitumor effect.…”
Section: Targeting Tamssupporting
confidence: 64%
See 1 more Smart Citation
“…The use of CSF-1R inhibitors in AML patients can inhibit the secretion of multiple cytokines in support cells and block their protective effects on AML cells. Similarly, our research also shows that targeting macrophages can delay the progression of ALL in mice [42]. Therefore, targeting CSF-1R combined with chemotherapeutic drugs can simultaneously kill leukemia cells, destroy the bone marrow microenvironment that they depend on for survival and enhance the antitumor effect.…”
Section: Targeting Tamssupporting
confidence: 64%
“…Recent studies have found that TAMs also have a significant impact on leukemia, including AML, chronic lymphocytic leukemia (CLL) and ALL, and can promote the survival, growth and drug resistance of leukemia cells [40][41][42]. Yahya et al (2016) found that the proportion of CD163 + CD206 + M2-like macrophages in the bone marrow of AML patients was significantly higher than that of healthy volunteers.…”
Section: Macrophages and Leukemiamentioning
confidence: 99%
“…CSF-1R signaling is another important pathway for TAM recruitment and differentiation [ 74 , 160 , 161 , 162 ]. It was demonstrated that CSF-1R inhibition could block TAM polarization in T-ALL mouse models [ 160 ].…”
Section: New Perspectives and Possible Tam-related Treatment Approachmentioning
confidence: 99%
“…CSF-1R signaling is another important pathway for TAM recruitment and differentiation [ 74 , 160 , 161 , 162 ]. It was demonstrated that CSF-1R inhibition could block TAM polarization in T-ALL mouse models [ 160 ]. A treatment combination between vincristine and a CSF-1R inhibitor could improve survival in leukemic T-ALL mice compared to vincristine as a singleagent [ 160 ].…”
Section: New Perspectives and Possible Tam-related Treatment Approachmentioning
confidence: 99%
See 1 more Smart Citation